Professor Emma Whitelaw, a pioneer of epigenetic inheritance - Ashe, Alyson; Hawes, Jessica J (Frontiers in Epigenetics and Epigenomics, 2026)
Here we explore the contribution of Professor Emma Whitelaw to the fields of epigenetics and transgenerational epigenetic inheritance. We highlight some recent advances to the field, while integrating the work of Professor Whitelaw and her team within our current understanding of epigenetic mechanisms.